The causality between obstructive sleep apnea and ventricular structure and function: a bidirectional Mendelian randomization study - Sun, Wanli; Yang, Fan; Yang, Yiyuan; Su, Xin; Xing, Yanwei (Frontiers in Genetics, 2023)
Multiple observational studies have discovered a substantial link between obstructive sleep apnea (OSA) and ventricular dysfunction. However, conventional observational studies are vulnerable to causal reversal and confounding, making it challenging to infer the causes of effects and their direction.With the help of a bidirectional, two-sample Mendelian randomization (MR) study, we assessed the potential causality between OSA and left and right ventricular (LV, RV) structure and function.We conducted our analysis utilizing summary data from genome-wide association studies of OSA (16,761 cases and 201,194 controls) in the FinnGen Study, as well as LV (36,041 participants) and RV (29,506 participants) in the UK Biobank cardiovascular magnetic resonance research. The inverse variance weighted (IVW) was selected as the main strategy, with the MR-Egger and 2 weighted median methods serving as supplements. Other methods were employed as sensitivity analysis tools to look at heterogeneity and pleiotropy, including MR-Egger intercept, Cochran Q statistic, MR-PRESSO, and leave-one-out analysis.In the primary IVW analysis, genetically predicted OSA was strongly causative on LV enddiastolic volume (β = 0.114, 95% CI = 0.034 ~0.194, P = 0.006) and LV stroke volume (β = 0.111, 95% CI = 0.031 ~0.191, P = 0.007), and genetically predicted LV ejection fraction was linked to an increased risk of OSA (OR = 1.161, 95% CI = 1.029 ~1.309, P = 0.015). However, there was no connection found between OSA and any RV parameters.Our genetic analysis raises a potential causative link between OSA and ventricular structure and function, which may improve the knowledge of OSA as a risk factor for cardiovascular disease by demonstrating a direct impact on cardiac structure and function.